Алгоритм визначення уподобань клієнтів CRM-систем - Тихенко, О. В. (ХНУРЕ, 2023)
The subject of research in the article is the process of ranking selection objects in the lists of recommendation subsystems of CRM systems. The purpose of the study is to improve the effectiveness of recommendations by improving the algorithm for determining preferences between objects in lists of objects of choice using the theory of multi-criteria decision-making. The proposed algorithm based on the method of comparative identification allows taking into account multiple characteristics of the objects of choice, has a lower time complexity than the algorithms of joint filtering methods.
Keywords: CRM systems; algorithms; method of comparative identification